Comparison of the major polyphenols in mature Argan fruits from two regions of Morocco - Khallouki, Farid; Breuer, Andrea; Ulrich, Cornelia; Owen, Robert (Food chemistry, 2017)
Previous studies have shown that Argan fruits contain a large variety of polyphenolic compounds. Recently, another class of polyphenolic compounds, namely amino phenols have been detected and identified in immature Argan fruits. The objective of this study, was to establish whether or not, these novel compounds are also present in mature Argan fruits. To this end, a comparison was made between mature fruits from two regions of Morocco. Nineteen major compounds were identified and quantitated, including amino phenols, flavonoids, and phenolic acids by chromatographic methods in mature Argan fruits from the two regions of Morocco (Essaouira and Agadir). The phenolic acids were identified as gallic acid and 3,4-dihydroxybenzoic acid; the amino phenols as Arganimide A, and argaminolics A-C, and the flavonoids as rutin pentoside, quercetin-3-O-arabinoside, quercetin glycogallate, quercetin-3-O-rhamnogalactoside, rutin, quercetin-3-O-galactoside (hyperoside), quercetin-3-O-glucoside (quercitrin), quercetin-3-O-arabinoside, quercetin glycohydroxybenzoate, quercetin glycosinapate, quercetin glycoferulate, quercetin glycocoumarate and quercetin. n=145.